The wireless data drain of users, apps, & platforms - Sani, Ardalan Amiri; Tan, Zhiyong; Washington, Peter; Chen, Mira; Agarwal, Sharad; Zhong, Lin; Zhang, Ming (ACM MC2R, 2013)
Cellular data consumption is an important issue for users and network operators. However, little is understood about data consumption differences between similar apps, smartphone platforms, and different classes of users. We examine data consumption behavior in the lab, comparing different apps of the same category, comparing the same top apps across different platforms, and comparing network APIs that apps use across different platforms. We also collect data from 387 Android users in India, where users pay for cellular data consumed, with little prevalence of unlimited data plans. Our ﬁndings can inform users on how their choice of platform and apps has a drastic impact on their data bill. Our ﬁndings can also inform operators on how to use incentives to induce desired data consumption.